Epistemología de la evaluación educativa desde la teoría de complejidad - Pulamarín Quishpe, Juan José (2013)
This research: “Epistemology of the educational evaluation from the theory of Complexity”, highlights the deep relationship between the epistemologic field, the contribution of the theory of Complexity, and the influence of the Positive Sciences in the account of the evaluation of the teaching-learning process; stating a process of analysis regarding to the reductions in which the educational evaluation lays. Therefore, I highlight the importance of establishing epistemological considerations about the structure of the sciences, starting from an historical analysis of the scientific method that highlights Galilee’s and Aristotle’s models to visualize how the positive sciences in modernity emerge and they have become absolute methodically under mathematical and quantitative strict conditions as a result of a type of instrumental rationality.